Optimization of the role of community midwives in maternal nutrition education to prevent stunting during the first 1000 days of life - Indrawati Aris Tyarini; Trimaya Cahya Mulat (Edukasi Ilmiah Indonesia, 2025)
Stunting remains a major public health issue that threatens the quality of human resources, particularly in developing countries. One of the critical periods to prevent stunting is the First 1000 Days of Life (HPK), starting from conception until a child reaches two years old. This community service program aimed to optimize the role of community midwives in providing maternal nutrition education for pregnant women as an effort to reduce stunting prevalence. The method employed was participatory action through training, counseling sessions, and the development of educational media tailored to local cultural contexts. Community midwives were equipped with up-to-date knowledge and skills regarding balanced nutrition, micronutrient supplementation, and strategies to increase family awareness about food diversity. Counseling activities were carried out in small groups with interactive discussions, supported by leaflets and visual aids to facilitate better understanding. The results indicated an improvement in the knowledge and attitudes of both midwives and pregnant women. Midwives demonstrated greater confidence in delivering nutritional education, while pregnant women showed increased awareness of the importance of protein, iron, folic acid, and other essential nutrients for fetal growth. Furthermore, family involvement in supporting pregnant women’s dietary practices became more evident. This program highlights that empowering community midwives as local health educators can be a strategic approach to break the intergenerational cycle of malnutrition. Strengthening collaboration among health workers, local governments, and community leaders is essential to sustain the impact and ensure long-term stunting prevention efforts